2012
DOI: 10.2478/s13382-012-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella serovars isolated for the first time in Poland, 1995–2007

Abstract: Objectives: Almost each year, a few Salmonella serovars isolated for the first time are noted in Poland. Each such serovar should be regarded as potentially dangerous. Recognition of them and monitoring their occurrence and frequency of distribution in all sources is important to control salmonellosis, and is one of the roles of the National Salmonella Centre. Materials and Methods: Over 2000 Salmonella strains submitted to the National Salmonella Centre for reference identification were examined. All of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…We found that the prevalence of Salmonella serovars from five species of poultry were different, and the main serovars were S. Pullorum (chicken), S. Enteritidis (duck), S. Typhimurium (goose), S. Typhimurium (pigeon), and S. Saintpaul (turkey). Other studies indicated that the prevalent serovars of Salmonella were usually correlated with a specific species or region (25,26). The host specificity was not observed in this study since the serovars of S. Typhimurium, S. Enteritidis, S. Heidelberg, and S. Kentucky were isolated from nearly all of these five poultry species.…”
Section: Discussionmentioning
confidence: 53%
“…We found that the prevalence of Salmonella serovars from five species of poultry were different, and the main serovars were S. Pullorum (chicken), S. Enteritidis (duck), S. Typhimurium (goose), S. Typhimurium (pigeon), and S. Saintpaul (turkey). Other studies indicated that the prevalent serovars of Salmonella were usually correlated with a specific species or region (25,26). The host specificity was not observed in this study since the serovars of S. Typhimurium, S. Enteritidis, S. Heidelberg, and S. Kentucky were isolated from nearly all of these five poultry species.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have reported that fresh edible leaves and cold-blooded animals were reservoirs for S. Uzaramo [36]. Only a few cases of human infection caused by S. Uzaramo have been reported in the USA and Poland [18, 36], but these lacked clear clinical descriptions. The invasive syndrome observed might also be a result of an immunological condition or medical history of the particular patient, i.e.…”
Section: Discussionmentioning
confidence: 99%
“… Salmonella consists of an array of diverse serovars, affecting a wide range of cold- and warm-blooded animals, including humans. Previous studies have reported that fresh edible leaves and cold-blooded animals were reservoirs for S. Uzaramo [ 36 ]. Only a few cases of human infection caused by S. Uzaramo have been reported in the USA and Poland [ 18, 36 ], but these lacked clear clinical descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional serotyping (White–Kauffmann–Le minor scheme) has been used as a Salmonella subtyping method for >80 years ( Salmonella Subcommittee of the Nomenclature Committee of the International Society for, Microbiology, 1934; Grimont and Weill, 2007; Guibourdenche et al, 2010; Dera-Tomaszewska, 2012; Shi et al, 2015) and has been a certified approach for public health monitoring of Salmonella infections for over 50 years (CDC, 2015). This method classifies the genus Salmonella into serovars (also known as “serotypes”) based on surface antigens including somatic (O), flagellar (H), and capsular (Vi) antigens (Brenner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%